Anti-stigma advocacy for health professionals: a systematic review - Guerrero, Zoe; Iruretagoyena, Barbara; Parry, Sarah; Henderson, Claire (Journal of mental health (Abingdon, England), 2024)
BACKGROUND: Many anti-stigma programs for healthcare workers already exist however there is less research on the effectiveness of training in skills for health professionals to counter stigma and its impacts on patients. AIMS: The objective of this study was to examine the theory base, content, delivery, and outcomes of interventions for healthcare professionals which aim to equip them with knowledge and skills to aid patients to mitigate stigma and discrimination and their health impacts. METHODS: Five electronic databases and grey literature were searched. Data were screened by two independent reviewers, conflicts were discussed. Quality appraisal was realized using the ICROMS tool. A narrative synthesis was carried out. RESULTS: The final number of studies was 41. In terms of theory base, there are three strands - responsibility as part of the professional role, correction of wrongful practices, and collaboration with local communities. Content focusses either on specific groups experiencing health-related stigma or health advocacy in general. CONCLUSIONS: Findings suggest programs should link definitions of stigma to the role of the professional. They should be developed following a situational analysis and include people with lived experience. Training should use interactive delivery methods. Evaluation should include follow-up times that allow examination of behavioural change. PROSPERO, ID: CRD42020212527.
Keywords: healthcare professionals; systematic review; Health Personnel; ochrana zájmů pacientů; lidé; Patient Advocacy; Social Stigma; Anti-stigma; advocacy; společenské stigma; zdravotnický personál; Humans